Synthesis, Characterization and Catalytic Activity of NiO-CoO-MgO Nano-Composite Catalyst - Salih Hadi Kadhim; Tariq Hussein Mgheer; Hussein Idrees Ismael; Khudheyer Jawad Kadem; Ahmed Saadon Abbas; Abbas Jasim Atiyah; Iman Jassim Mohamad (Universitas Gadjah Mada, 2019)
The ternary NiO-CoO-MgO catalyst in three ratios 20:20:60, 25:25:50, and 30:30:40 for these component oxides respectively, were synthesized by co-precipitation method of their carbonates by addition of a precipitate agent in basic media, and then calcinated these carbonate to obtain of mixed oxides. The prepared catalysts were characterized by using Powder X-Ray Diffraction (PXRD), Fourier Infrared spectroscopy (FT-IR), and Atomic Force Microscopy techniques (AFM) were used for identification of the prepared catalysts. The result showed that the particle size of these catalyst ratios, were in the nano range and the smallest size was 25:25:50. The investigation of catalytic activity of prepared catalysts was done by photo decolorization of Celestine blue B dye from simulated industrial wastewaters in aqueous solution. The decolorization efficiency of dye reached 99.9% after irradiation time for 1 h. Study the effect of different reaction conditions such as the pH of the medium, the weight of semiconductor and temperature of mixture reaction were shown that the maximum degradation was observed in conditions at pH = 4, catalyst dosage = 0.08 g, and temperature = 303 K.